2022-RA-1689-ESGO Should immunotherapy be included as first-line adjuvant treatment in high-risk vulvar melanomas?. (20th October 2022) - Benito, Virginia; Molo, Cristina; Lubrano, Amina; García, Pino; Bohn, Uriel
Abstract : Introduction/Background: Melanoma of the female lower genital tract is a rare and aggressive disease, with poor long-term clinical outcomes. Although rare, vulvar melanoma is the second most common histological type of vulvar cancer, representing 7–10% of all malignant vulvar neoplasms. Methodology: Management of vulvar malignant melanoma is challenging. No unified, effective, and standardized treatment plan has been established for this disease. Radiation therapy and chemotherapy do not seem to benefit survival. In fact, there is still no consensus on the use of adjuvant therapy and only a single case series and few case reports on this topic are available. Encouragingly, accumulating evidence supports the role of immunotherapy in improving survival of patients with metastatic melanoma however, there is no evidence of its use in relation to patients with high-risk melanoma as first-line adjuvant therapy. Results: We herein describe the preoperative, postoperative and follow-up clinical data of two patients with the diagnosis of high-risk vulvar malignant melanoma, 6-mm and 4, 2-mm Breslow depth, respectively. Both of them underwent radical surgery consisting of radical vulvectomy and inguinal lymphadenectomy. Histopathological study revealed that the margins of the surgical pieces were free of disease and the inguinal staging was negative. No adjuvant therapy was proposed in multidisciplinary committee due to the lack of scientific evidence. However, very soon after radical surgery, they presented with recurrent disease and extensive metastasic disease. Conclusion: Malignant vulvar melanoma has a poor prognosis not only for those with regional and distant metastatic disease but also for patients with high-risk disease. The use of immunotherapy has increased over time and may improve survival in those with distant disease. The current dilemma is the lack of consensus on its use after surgery, even in high-risk patients. These data support further investigation into the role of immunotherapy for vulvar melanoma to optimize outcomes.